STRATEGI BERTAHAN HIDUP PENGRAJIN BATU ALAM YANG TERGABUNG DALAM PAGUYUBAN â KARYA STONE â DI DESA SAMBIREJO PRAMBANAN SLEMAN - , ODI ANWAR P., Krisdyatmiko, S.Sos., M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Small craft natural stone industry is a business that is occupied by some residents in Sambirejo that can provide an increase in the family economy. Where at first there were only 3 natural stone craft factory and to date there are 21 factories that have sprung up in the area Sambirejo. In development, this effort can not be separated from the tides due to the various problems experienced. Among the rising cost of production, wages manpower and a lot of effort sprung the same natural stone craft in regions outside Sambirejo, as in Cangkringan, probably volcanic, Ponjong, and Semin. With natural stone business banyakanya the emerging influential terghadap existence of natural stone craftsmen in Sambirejo. So the natural stone craftsmen in Sambirejo requires some strategy to maintain the continuity of their business. This study took place in the village located in the district Sambirejo Prambanan, Sleman, Yogyakarta. The village has the potential of natural resources in the form of rocks and stones among which palimanan breccia rocks (yellow) are relatively abundant. This study used a qualitative approach with descriptive analysis as the method of choice. Informants involved in this study are numbered twelve, two informants are employees of the village, seven natural stone craft business owner and three workers in Sambirejo natural stone crafts. Decision aims informant conducted (purposive) that has been determined in advance. Data were collected through observations, interviews and documentation of the natural stone craftsmen in Sambirejo. Based on the results of the research, it is known that the presence of natural resources in the village have Sambirejo then comes the many natural stone handicraft business in ilayah Sambirejo. Increasing number of craftsmen of natural ston , then came the idea to set up a community \" STONE WORKS \". Where community \"STONE WORKS\" This serves to memadahi many natural stone craftsmen in Sambirejo strategies that appear useful in the natural stone business survival. Stratrgi-strategies include: Expansion of natural stones network among entrepreneurs, maintaining customer satisfaction by maintaining quality of products and services, establish a cooperative association, Deversivikasi product, and price fixing. The strategies implemented by the community \"STONE WORKS\" is very useful for entrepreneurs that are in the natural stone Sambirejo region. The entrepreneur can survive in the field of natural stone mengeluti efforts, they can overcome the problems faced. Given current natural stone that many businesses have sprung up outside the Sambirejo.